Optimal distribution of agents in crop spraying (2020)
The use of UAV in agriculture decreases pesticide waste and increase spray speed. Multiple UAV distribution methods for crop spraying consider nozzle dynamics and the non-uniform of the desired spray. However, these do not restrict the energy consumption of the agents that is an important restriction in UAV systems. We propose a new methodology to decrease deployment time while the spraying error is minimal. The distribution method used is Heat Equation Driven Control (HEDAC) which is focused on non-uniform spraying. We change the method to improve the low-level control dynamics and ensure convergence. The simulations consider two desired density function: uniform and non-uniform. In all cases, the method considers a collision-avoidance that allows agents to move freely without affecting performance. The results show that not all agents need the same deployment time to achieve good performance. Overall flight time is shorter reducing energy consumption.